Evaluating the potential for Blue-Green Infrastructure benefits using the case study of stormwater ponds in Cape Town, South Africa - Fell, Jessica (Department of Civil Engineering, 2024)
A Water Sensitive City (WSC) is increasingly being pursued to deliver on various sustainability, resilience and liveability goals. Expanding Blue-Green Infrastructure (BGI) is a major step towards a WSC. BGI can provide multiple social and environmental benefits, from increased amenity to enhanced biodiversity to urban heat reduction. However, the expansion of BGI is not always feasible. This is particularly true in many Global South contexts with rapidly urbanising cities characterised by patterns of informality, inadequate infrastructure and service delivery provision, competition for space and increasing resource pressures. In such contexts, existing blue infrastructure (BI), i.e., natural or artificial water bodies such as rivers, canals, ponds, streams, wetlands and stormwater drainage provision, can be transformed to provide multiple benefits as BGI. This study presents a Multi-Criteria Analysis (MCA) methodology to evaluate the potential for existing BI to provide multiple benefits as BGI. The MCA methodology was developed through the case study of the City of Cape Town, South Africa. The multifunctional potential of the city's existing stormwater ponds, of which there are over 800, was evaluated. This was a contribution towards the city's 2020 Water Strategy commitment to ‘become a Water Sensitive City' by 2040 with multifunctional infrastructure. Using value-focused thinking, the MCA methodology incorporated seven benefits framed as WSC planning priorities: (1) ‘Enhancing cultural and heritage associations with water systems', (2) ‘Increasing water re- use', (3) ‘Reducing the Urban Heat Island (UHI) effect', (4) ‘Enhancing community services connections with water systems', (5) ‘Increasing access to blue-green space', (6) ‘Incorporating stormwater quality limitations', and (7) ‘Enhancing biodiversity'. A pilot MCA was conducted to assist the process. An associated criterion was selected for each WSC planning priority through semi-structured interviews with WSC experts in Cape Town. The criteria were scored, and stakeholder weights were obtained using three weighting methods: rating, ranking and pairwise comparison. A weighted additive model was used to combine the scores and weights. Ponds with a high potential to provide a combination of the seven benefits were identified. The relative prioritisation of the ponds for the individual and combined criteria were mapped in a Geographic Information System (GIS) to allow for the visualisation of the rankings. Synergies and trade-offs were assessed using Pearson correlation coefficients between criterion scores. In Cape Town, the ‘Enhancing community services connections with water systems' WSC planning priority had the largest number of high scoring ponds, with 36% within 290 m of a school, community centre or religious institution. Of the ponds, 12% had a high potential for Managed Aquifer Recharge for ‘Increasing water re-use'. This was largely because they overlie a shallow sandy primary aquifer in the city. For ‘Incorporating stormwater quality limitations', almost half of the ponds (46%) were within 200 m of a potentially contaminating activity (informal settlement, industrial, road, landfill, wastewater treatment works land cover). This indicated potential constraints to multifunctionality from poor stormwater quality. Synergies between ‘Increasing water re-use' and ‘Reducing the UHI', ‘Enhancing community services connections with water systems' and ‘Enhancing biodiversity' were indicated through statistically significant positive correlations. This helps to identify ponds for strategic prioritisation to leverage co-benefits. However, negative correlations revealed the trade-offs that prioritising ponds for ‘Increasing access to blue-green space' and ‘Increasing water re-use' may not be well suited to ‘Incorporate stormwater quality limitations'. Stakeholders regarded the benefits of ‘Increasing access to blue-green space' and ‘Increasing water re-use' as the most important across the weighting methods. The combined criteria using the different weighting methods indicated a hotspot of ponds with the highest relative multifunctional potential in the southern central part of the city. These ponds would be the highest priority for multifunctional transformation to maximise benefits as BGI for a WSC. The MCA methodology paired with GIS visual capabilities provides a strategic and participatory approach to evaluating the potential for existing BI to provide multiple benefits as BGI towards a WSC. Applying this methodology to Cape Town's existing stormwater ponds illuminated their multifunctional potential. The MCA methodology is transferrable as the WSC planning priorities are relevant to many urban Global South contexts. It is flexible, able to incorporate different benefits, and the steps could be customised for different types of BI.